67.1: Distinguished Student Paper: 40 um‐pitch IGZO TFT Gate Driver for High‐resolution Rollable AMOLED. Issue 1 (1st July 2013) - Geng, Di; Kim, Byung Soon; Mativenga, Mallory; Seok, Man Ju; Kang, Dong Han; Jang, Jin
Abstract: We report the design and fabrication of an amorphous‐indium‐gallium‐zinc‐oxide (a‐IGZO) thin‐film transistor (TFT)‐based high‐speed and ultra‐narrow shift register on a plastic substrate. The shift register consisting 5 TFTs and 1 capacitor is small in physical size which is only 40 μm in width (pitch). At the supply voltage (VDD) of 15 V, the clock frequency of the shift register approaches 166.7 kHz, corresponding to a pulse width of 3 μs. The shift register could be operated under mechanical bending radius of 2mm, making it applicable to flexible high resolution active‐matrix displays.